2022
DOI: 10.15406/jamb.2022.11.00335
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Biological Features of a Mugilidae Chelon Ramada in Two Tunisian Reservoirs

Abstract: Mullet is the most massively harvested species, representing the third of the total freshwater fish landing in Tunisia. To ensure freshwater fish farming durability and development in the country, reservoirs have been stocked with Mugilidae fry which was collected from coastal and estuaries areas after a short adaptation period. The objective of this paper is to compare and contrast Chelon ramada’’s age, growth, and mortality in two Tunisian freshwater reservoirs (Seliana and Kasseb). The sample species were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These are used to stock freshwater reservoirs [1,13]. Until 2009, several species of Mugilidae were introduced as fry into many Tunisian reservoirs [7,[26][27][28]. The fry of M. cephalus and C. ramada, collected from coastal and estuary areas, were acclimated and introduced into the reservoirs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These are used to stock freshwater reservoirs [1,13]. Until 2009, several species of Mugilidae were introduced as fry into many Tunisian reservoirs [7,[26][27][28]. The fry of M. cephalus and C. ramada, collected from coastal and estuary areas, were acclimated and introduced into the reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…The fry of M. cephalus and C. ramada, collected from coastal and estuary areas, were acclimated and introduced into the reservoirs. These species revealed normal survival conditions, but they were unable to reproduce in freshwater [1,26,29,30]. Previous research on mullet fry exploitation in Tunisian waters revealed that lowland courses had a very high density of fry migrating from the open sea to estuarine waters depending on their intensity and physicochemical water parameters.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations